Pengaruh Penggunaan Multimedia Pembelajaran Interaktif terhadap Hasil Belajar Siswa Kelas XI pada Mata Pelajaran Ekonomi di SMA Negeri 4 Gorontalo - Reka Hamid; Roy Hasiru; Abdulrahim Maruwae; Frahmawati Bumulo; Imam Prawiranegara Gani (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to identify the influence of utilizing interactive learning multimedia on the learning outcomes of class XI students in the economics subject at SMA Negeri 4 Gorontalo. This research employs a quantitative approach with a quasi-experimental design. The total sample consists of 60 students.The findings indicate that there is an influence of utilizing interactive learning multimedia on the learning outcomes of class XI students in the economics subject This is shown through data analysis using a paired sample t-test, which resulted in a significance value (Sig. 2-tailed) of 0 000. This value is far below the predetermined significance level of 005, indicating a significant difference between students' learning outcomes before and after utilizing interactive multimedia, as well as a significant difference between the experimental class (utilizing multimedia) and the control class (not utilizing multimedia). Therefore, the utilization of interactive learning multimedia not only provides variety in the teaching and learning process but also contributes meaningfully to improving students' conceptual understanding, material retention, and learning motivation.